1998
DOI: 10.1897/1551-5028(1998)017<1730:bopahb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Polycyclic Aromatic Hydrocarbons by Earthworms: Assessment of Equilibrium Partitioning Theory in in Situ Studies and Water Experiments

Abstract: Abstract-The purpose of this study was to assess the suitability of applying equilibrium partitioning (EqP) theory to predict the bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) by earthworms when these are exposed to contaminated soils in the field. Studies carried out in situ in various contaminated floodplain sites showed the presence of linear relationships with intercept zero between the lipid-normalized concentration of different PAHs in the earthworm Lumbricus rubellus and the organic-mattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 0 publications
5
37
0
Order By: Relevance
“…Dolfing and Bril [1] have made the interesting suggestion that the intersite variation in the biota‐soil accumulation factor (BSAF) for polycyclic aromatic hydrocarbons (PAHs) in earthworms as described in our study [2] can be attributed to variations in clay content (fraction <2 μm) and pH. They hypothesize that clay enhances the bioavailability of PAHs to earthworms by influencing the sorption of these compounds to organic matter or, as another possibility, that PAHs sorbed to clay are more bioavailable.…”
mentioning
confidence: 59%
“…Dolfing and Bril [1] have made the interesting suggestion that the intersite variation in the biota‐soil accumulation factor (BSAF) for polycyclic aromatic hydrocarbons (PAHs) in earthworms as described in our study [2] can be attributed to variations in clay content (fraction <2 μm) and pH. They hypothesize that clay enhances the bioavailability of PAHs to earthworms by influencing the sorption of these compounds to organic matter or, as another possibility, that PAHs sorbed to clay are more bioavailable.…”
mentioning
confidence: 59%
“…The equilibrium partitioning theory [1] states that the biota‐soil accumulation factor (BSAF) of organic chemicals is independent of the octanol/water partitioning coefficient ( K ow ). Ma et al [2] recently presented a valuable dataset that fully supports this theory. In a series of field studies, these authors measured the bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) by earthworms and concluded that “The partitioning of PAHs between the worm lipid phase and soil organic carbon conformed to a linear relationship with intercept zero.…”
Section: To the Editormentioning
confidence: 83%
“…This suggests that the soil properties of the different sites affected the BSAF. We were surprised, and indeed challenged, by the statement of Ma et al [2] that no significant correlations were present between the BSAF and the soil properties measured, which included pH (KCl), CaCO 3 and soil organic matter (SOM) content, and grain‐size fractions (Table 1). Linear regression on the (log of) the four soil parameters listed in Table 1 indeed did not yield meaningful results (e.g., Fig.…”
Section: To the Editormentioning
confidence: 90%
See 1 more Smart Citation
“…Earthworms are typical soil inhabitants making up > 80% of the biomass of soil macrofauna (Yasmin and D'Souza, ), and are frequently found in the rhizosphere environment (Springett and Gray, ). Earthworms can survive in the most highly contaminated soils as only water soluble compounds can be absorbed through their skin (Jager, ), which excludes most toxic PAHs (Ma et al ., ) and PCBs (Beyer and Stafford, ). For instance, Zavala‐Cruz et al .…”
Section: Soil Organismsmentioning
confidence: 99%